2018
DOI: 10.1051/epjconf/201817002099
|View full text |Cite
|
Sign up to set email alerts
|

The heat transfer coefficient determination with the use of the Beck-Trefftz method in flow boiling in a minichannel

Abstract: Abstract. In this paper, the solution of the two-dimensional inverse heat transfer problem with the use of the Beck method coupled with the Trefftz method is proposed. This method was applied for solving an inverse heat conduction problem. The aim of the calculation was to determine the boiling heat transfer coefficient on the basis of temperature measurements taken by infrared thermography. The experimental data of flow boiling heat transfer in a single vertical minichannel of 1.7 mm depth, heated asymmetrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…4c,d) in the outlet section of the minichannel. Similar dependencies were observed by Strąk et al in [5], where markedly higher local heat transfer coefficients were also observed at lower mass flux in the saturated boiling region. The boiling curves in Figs.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4c,d) in the outlet section of the minichannel. Similar dependencies were observed by Strąk et al in [5], where markedly higher local heat transfer coefficients were also observed at lower mass flux in the saturated boiling region. The boiling curves in Figs.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies of the authors examined other methods for determining the local heat transfer coefficient in two-dimensional approaches, using the Trefftz or Beck methods obtained from solving the inverse problem [4,5,9,12,[34][35][36][37][38].…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation